In vitro and in vivo evaluation of the biofilm-degrading Pseudomonas phage Motto, as a candidate for phage therapy - Manohar, Prasanth; Loh, Belinda; Turner, Dann; Tamizhselvi, Ramasamy; Mathankumar, Marimuthu; Elangovan, Namasivayam; Nachimuthu, Ramesh; Leptihn, Sebastian (Frontiers in Microbiology, 2024)
Infections caused by Pseudomonas aeruginosa are becoming increasingly difficult to treat due to the emergence of strains that have acquired multidrug resistance. Therefore, phage therapy has gained attention as an alternative to the treatment of pseudomonal infections. Phages are not only bactericidal but occasionally show activity against biofilm as well. Here, we describe the Pseudomonas phage Motto, a T1-like phage which has the ability to clear P. aeruginosa infections in an animal model and also exhibited biofilmdegrading properties. The phage has substantial antibiofilm activity against strong biofilmproducing isolates (n = 10), with at least a 2-fold reduction within 24 hours. To demonstrate the safety of using phage Motto, we performed cytotoxicity studies with human cell lines (HEK 293 and RAW 264.7 macrophages). Using a previously established in vivo model, we demonstrated the efficacy of Motto in Caenorhabditis elegans, with a 90% survival rate when treated with the phage at a Multiplicity of Infection of 10.Phages are often evaluated mainly on their ability to kill bacterial hosts. One important aspect, however, is often neglected: Their ability to degrade biofilms. Not all phages are able to disintegrate biofilms. While phages can kill planktonic cells, it also has often been observed that phages are not able to infect those that are embedded in biofilms. Phage Motto appears to have highly efficient enzymes that degrade biofilms, and might therefore be a highly valuable therapeutic candidate.